2014
DOI: 10.1016/j.devcel.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules Regulate Focal Adhesion Dynamics through MAP4K4

Abstract: Disassembly of focal adhesions (FAs) allows cell retraction and integrin detachment from the ECM, processes critical for cell movement. Growth of MT (microtubule) can promote FA turnover by serving as tracks to deliver proteins essential for FA disassembly. The molecular nature of this FA “disassembly factor”, however, remains elusive. By quantitative proteomics, we identified MAP4K4 (mitogen-activated protein kinase kinase kinase kinase 4) as a FA regulator that associates with MTs. Conditional knockout (cKO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
142
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 35 publications
(91 reference statements)
17
142
4
1
Order By: Relevance
“…Keratinocytes lacking MAP4K4 exhibited reduced Arf6 activation, increased surface b1 integrin expression, enlarged focal adhesions and a reduced rate of b1 integrin internalization, essentially phenocopying BRAG2 depletion. 23 Although these data suggest that phosphorylation of BRAG2 by MAP4K4 may stimulate its catalytic activity, this remains to be tested directly. Interestingly, these authors found that rapid cycling Arf6T157A is capable of normalizing focal adhesion dynamics in keratinocytes lacking either MAP4K4 or BRAG2, suggesting that Arf6 is an essential effector of this pathway.…”
Section: Integrin Traffickingmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratinocytes lacking MAP4K4 exhibited reduced Arf6 activation, increased surface b1 integrin expression, enlarged focal adhesions and a reduced rate of b1 integrin internalization, essentially phenocopying BRAG2 depletion. 23 Although these data suggest that phosphorylation of BRAG2 by MAP4K4 may stimulate its catalytic activity, this remains to be tested directly. Interestingly, these authors found that rapid cycling Arf6T157A is capable of normalizing focal adhesion dynamics in keratinocytes lacking either MAP4K4 or BRAG2, suggesting that Arf6 is an essential effector of this pathway.…”
Section: Integrin Traffickingmentioning
confidence: 99%
“…At the molecular level, MAP4K4 phosphorylates moesin, which then displaces talin from b1-integrin-containing focal adhesions, eventually leading to focal adhesion disassembly. 27 Together with the work by Yue et al 23 this suggests a model in which MAP4K4 is delivered to focal adhesions by microtubules where it cooperates with BRAG2 and Arf5 (or Arf6) to release b1-integrins from focal adhesions. Future work will be required to dissect out the precise roles of each component in adhesion turnover.…”
Section: Brags and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…While the major cytoskeletal element associated with FAs is actin, microtubules also play an important role in adhesion by regulating the FA turnover Byron et al, 2015;Kaverina et al, 1999Kaverina et al, , 1998Krylyshkina et al, 2003;Small and Kaverina, 2003;Stehbens and Wittmann, 2012;Yue et al, 2014). The recent proteomics work showed that microtubule-FA cross-talk strongly depends on the activation state of the integrins (Byron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, the three MT end-binding proteins, EB1, EB2 and EB3, share substantial sequence homology, but while EB1 and EB3 promote MT growth by suppressing catastrophe, EB2 does not play a direct role in MT dynamic instability (34,35). Recent work has proposed that EB2 plays an essential role in the regulation of focal adhesion dynamics and cell migration via its interaction with the kinase MAP4K4 (36). EB3 is expressed preferentially in the central nervous system and muscle, while EB1 is ubiquitously expressed (37).…”
Section: Microtubule Plus-end Tracking Proteins (+ Tips)mentioning
confidence: 99%